Early Adolescent Problem Behavior - Suzanna Smith (EDIS, 2012)
“You’ve probably known a parent of a middle-schooler who has lamented that aliens abducted their sweet child and returned a different, not so sweet preteen being. Early adolescence is a time of change in the relationship between parent and adolescent, and both have to adjust. Although most families weather these changes without serious difficulties, some families do have problems…” This transcript of a two-minute Family Album Radio broadcast was published by the UF Department of Family, Youth and Community Sciences, March 2012.